2019
DOI: 10.1021/acs.analchem.9b02382
|View full text |Cite
|
Sign up to set email alerts
|

Improving Electrochemical Pb2+ Detection Using a Vertically Aligned 2D MoS2 Nanofilm

Abstract: Recent advancements in MoS 2 nanofilms have aided in the development for important water-related environmental applications. However, a MoS 2 nanofilm-coated sensor has yet to have been applied for heavy metal detection in water-related environmental samples. In this study, a novel vertically aligned two-dimensional (2D) MoS 2 (edge exposed) nanofilm was applied for in situ lead ion (Pb 2+ ) detection. The developed sensor showed an excellent linear relationship toward Pb 2+ between 0 and 20 ppb at −0.45 V vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…As shown in Figure c, compared with the reference bilayer structure, for the bowl-like MoS 2 structure, the total potential of the top ring layers lifts up and the potential barrier along the layer-normal direction in bowl-like MoS 2 has reduced. The calculated results of the total electrostatic potential are in good agreement with the other theoretical calculations. , As shown in Figure d, electrons in the ferromagnetic bowl-like MoS 2 could be more sensitive to the external magnetic field and obtain extra energy MH compared to those in nonmagnetic bilayer MoS 2 under external vertical magnetic field H . The electrons in the bowl-like MoS 2 structure are easier to transport due to possessing a higher energy than those in bilayer MoS 2 .…”
supporting
confidence: 86%
“…As shown in Figure c, compared with the reference bilayer structure, for the bowl-like MoS 2 structure, the total potential of the top ring layers lifts up and the potential barrier along the layer-normal direction in bowl-like MoS 2 has reduced. The calculated results of the total electrostatic potential are in good agreement with the other theoretical calculations. , As shown in Figure d, electrons in the ferromagnetic bowl-like MoS 2 could be more sensitive to the external magnetic field and obtain extra energy MH compared to those in nonmagnetic bilayer MoS 2 under external vertical magnetic field H . The electrons in the bowl-like MoS 2 structure are easier to transport due to possessing a higher energy than those in bilayer MoS 2 .…”
supporting
confidence: 86%
“…This challenge has been the major limiting factor in terms of fully exploring technological opportunities of VA 2D-TMD layers beyond their growth substrate-bound forms. In general, VA 2D-TMD layers exhibit unparalleled chemical reactivity and physisorption properties owing to their surface-exposed rich dangling bonds, suggesting great implications for high-performance electrochemical and/or molecular sensing applications. , Such unprecedented opportunities can be realized even in flexible and/or stretchable forms as far as they are deterministically and stably integrated on mechanically reconfigurable yet functional substrates retaining their original structural integrity. Figure c illustrates schematics of our manufacturing strategy, which overcomes this limitation and can be generalized to 2D TMD layers of any layer orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, MoS 2 showed excellent adsorption performance for HMIs owing to the high binding affinity between divalent ions and its sulfur sites. Also, MoS 2 (molybdenum disulfide) was applied as an available adsorbing material and promoted the reduction of some ions into elements [15]. Gan [16] et al reported electrochemical sensor for Cd(II) detection based on MoS 2 nanosheets synthesized by liquid-phase exfoliation, the prepared sensor acquired high sensitivity and selectivity for Cd(II) detection.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, MoS 2 showed excellent adsorption performance for HMIs owing to the high binding affinity between divalent ions and its sulfur sites. Also, MoS 2 (molybdenum disulfide) was applied as an available adsorbing material and promoted the reduction of some ions into elements [15]. Gan [16] et al.…”
Section: Introductionmentioning
confidence: 99%